Behaviour settings theory applied to domestic water use in Nigeria: A new conceptual tool for the study of routine behaviour. (August 2019) - Curtis, Val; Dreibelbis, Robert; Buxton, Helen; Izang, Nancy; Adekunle, Dara; Aunger, Robert
Abstract: Rationale: Many behaviours relevant to public health are part of everyday routines. However, few tools exist to study such behaviours. Here we re-introduce the behaviour setting, an ecological psychological concept developed in the 1950s, as an approach to the study of routine behaviour. The setting concept bridges theoretical and applied approaches in sociology, psychology and social practice; its components include stage, infrastructure, props, roles, norms, competencies, objectives and resultant routines. Methods: We applied settings theory to health-related water use behaviour in rural Nigeria. We captured the dimensions of water use behaviour settings in 23 households at varying distances from newly-introduced kiosks selling purified water. Results: We found that routines concerning drinking, laundering, dish washing and handwashing were stable in their settings, varying little between households or by type of water source. Hygiene routines were suboptimal but drinking water was carefully segregated. The majority of water use behaviour was governed, not by an immediate desire to maximise health, but by long-established routines embedded in the social, technical and physical environment. Water kiosks are making only marginal improvements to the quantity and quality of water being used in homes. Conclusions: Improving public health will require the disruption of settings, for example, through bringing water infrastructure directly to the home, through the sale of new props that facilitate hygienic routines, or in the disruption of gender roles via the promotion of new norms. Settings are an ecologically valid, meso-level theoretical approach that link social and techno-physical environmental factors to behaviour. They provide a comprehensive framework within which to judge avenues for changing routine behaviours. The behaviour settings tool we developed was easy to use, provided a systematic means of capturing the determinants of routine behaviour, and the findings offered insight into methods for disrupting such behaviour. Highlights: Much health-relevant behaviour is routine and not consciously controlled. Behaviour settings theory provides a simple, new method to study routine behaviour. Components of settings include s tage, infrastructure, props, norms, and roles. Water use routines in rural Nigeria are stable but can be disrupted. Behaviour settings should be added as theoretical and investigative tools.